Changes in Human Meibum Lipid with Meibomian Gland Dysfunction using Principal Component Analysis - Borchman, Douglas (2010)
Changes in the phase transition temperatures and conformation of human meibum lipid with age and meibomian gland dysfunction have been quantified but with analysis of less than 1% of the infrared spectral range. The remaining 99 % of the spectral range was analyzed with principal component analysis (PCA) and confirms our previous studies and reveal further insights into changes that occur in meibum with age and disease. Infrared spectra of meibum from 41 patients diagnosed with meibomian gland dysfunction (Md) and 32 normal donors (Mn) were measured. Principal component analysis (PCA) was used to quantify the variance among the spectra and meibum protein was quantified using the infrared carbonyl and amide I and II bands. A training set of spectra was used to discriminate between Mn and Md with an accuracy of 93 %. This shows that certain spectral regions (eigenvectors) contain compositional and structural information about the component (variable), meibomian gland dysfunction. The spectral features of the major eigenvector indicate that Md contains more protein and relatively less CH(3) and cis=CH band intensity compared to Mn. The amount of protein was confirmed from relative infrared band intensities. Our study supports the idea that compositional differences result in meibum that is less fluid and more viscous with meibomian gland dysfunction so that less lipid flows out of the meibomian gland orifice as observed clinically. This study also demonstrates the power of the combination of infrared spectroscopy and PCA as a diagnostic tool that discriminates between Mn and Md.